TINGKAT KECEMASAN MAHASISWA DI RUANG ISOLASI MANDIRI UNIVERSITAS ADVENT INDONESIA - Parlindungan Manurung; Untung Sudharmono (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
Various efforts have been made by the government to stop the chain of spread of the Covid-19 virus, among others, by following health protocols, not panicking, maintaining health, avoiding crowds and maintaining distance, and strengthening the body's immunity. The low level of awareness of students who live in dormitories in following health protocols causes students to be exposed to the Corona virus so they have to undergo isolation or quarantine in the dormitory. People who are confirmed positive for Covid-19 who are isolated can experience mental disorders, such as anxiety. Therefore, this study was conducted to determine the anxiety level of students undergoing isolation at the Adventist University of Indonesia. This research method is descriptive quantitative. The subjects in this study were students who were exposed to the Covid-19 virus as many as 58 people. Saturated sampling techniques where the entire population was involved in the study. Instruments for measuring anxiety signs using the Hamilton Anxiety Rating Scale (HARS). This study showed that there were 37 students (63.8%) who were being treated in the isolation room were not experiencing anxiety. There were 19 students (32.8) experiencing mild anxiety and 2 students (3.4%) experiencing moderate anxiety. The majority of respondents experienced sleep pattern disorders, where students could not rest quietly, which was as many as 28 (48.2%).